Valutazione dinamica del fattore copertura del suolo (C-factor) della RUSLE attraverso immagini telerilevate. - Sergio Grauso (mediaGEO soc. coop., 2019)
A correlation analysis between mean Normalized Difference Vegetation Index (NDVI), derived from MODIS imagery time-series (2001-2016), and mean long-term cover management data derived from the C-factor map of the European Union, is here reported. The aim was to find out a model equation helpful to easily estimate the C-factor of the RUSLE by using the remotely sensed vegetation index as predictor. A sigmoid logistic function resulted to fit well with the observed data (R-square = 0.989, RMSE = 0.015). Two examples of simulations at annual timescale are provided, proving the versatility of the proposed model to estimate the C-factor at differently refined timescales and to easily draw updated maps basing on the availability of NDVI data-series.